Improving the Performance of a 4-Stroke Motorcycle with Variation Diameter and Mass Piston - Khambali, Khambali; Winoko, Yuniarto Agus; Choirun, Mochamad (Indonesian Journal of Advanced Research, 2024)
The purpose of this study was to determine the effect of variations in piston diameter and piston mass on the performance of a 4-stroke motorcycle. The method used is an experimental method with a quantitative approach. Data collection was carried out using the dynotest method, burret and stopwatch. The samples of this study are 3 types of pistons with different diameters where the piston mass varies to test the performance of a 4-stroke motorcycle including Torque, SFC (Specific Fuel Consumption) and BMEP (Break Mean Effective Pressure). The results of this study show that the p-value of the variation of piston diameter and mass is smaller than alpha p-value < alpha (0.05) which indicates that the variation of piston diameter and mass affects the performance of 4-stroke motorcycles.